Accountability Accounting as Achievement Measurement Tool for Profit Center Manager at UD. Meubel Mulya Jati Widang Tuban: Akuntansi Pertanggungjawaban Sebagai Alat Pengukur Prestasi Manager Pusat Laba Pada UD. Meubel Mulya Jati Widang Tuban - Novi Vizarifah; Louse Happy Amira Salatnaya; Syarifah Syarifah (Academia Open, 2019)
Accountability accounting is an accounting system that recognizes the various centers of responsibility in the whole company, which reflects the plans and actions of each responsibility center by determining certain revenues and costs. The purpose of this research is to explain the implementation and application of the profit center accountability accounting system as well as explaining the accountability accounting application system to assess the work performance of the profit center at UD. Mulya Jati Widang Tuban furniture. This type of research conducted by the author is descriptive analysis, namely a study to make a systematic, active and accurate description of a picture or painting regarding the factors, properties and relationships between the phenomena under study then compared with existing practices and conclusions drawn. Implementation and application of accounting system for profit center accountability accounting at UD. Meubel Mulya Jati, said to be good where there is an audit every year-end on the financial statements by each division where the calculation process is based on analysis of expenses / operational costs and sales results. Next, the performance of the profit center manager has increased every year.